2016
DOI: 10.1016/j.jim.2015.12.003
|View full text |Cite
|
Sign up to set email alerts
|

SLE-key® rule-out serologic test for excluding the diagnosis of systemic lupus erythematosus: Developing the ImmunArray iCHIP®

Abstract: We describe here the development, verification and validation of the SLE-key® rule-out test for a definitive rule-out of a diagnosis of systemic lupus erythematosus (SLE). The test uses the proprietary iCHIP® micro-array technology platform (Fattal et al., 2010) to identify discriminating patterns of circulating autoantibodies among SLE patients compared to self-declared healthy individuals. Given the challenges associated with the diagnosis of SLE and the healthcare costs of delayed diagnosis and misdiagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…Published data from an FDA-approved protein microarray showed that levels of IgG response to host proteins and EBV-encoded EBNA-1 protein and other viral proteins Table 4 IgG response was present to EBNA-1 protein A/T hook region GRPGAPGG (aa 51-57) 4 15 could diagnosis both SLE and scleroderma with sensitivity and specificity similar or greater to conventional ANA testing [15]. Addition of viral protein antigens in this assay significantly improved the sensitivity and specificity, although the specific IgG-binding epitopes recognized by immunoglobulin G were not disclosed [15,16]. In this work, IgG-binding results are presented derived from a proprietary laser-printed peptide microchip containing overlapping peptides from immunologically important EBV proteins to illustrate the potential of this new technology.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Published data from an FDA-approved protein microarray showed that levels of IgG response to host proteins and EBV-encoded EBNA-1 protein and other viral proteins Table 4 IgG response was present to EBNA-1 protein A/T hook region GRPGAPGG (aa 51-57) 4 15 could diagnosis both SLE and scleroderma with sensitivity and specificity similar or greater to conventional ANA testing [15]. Addition of viral protein antigens in this assay significantly improved the sensitivity and specificity, although the specific IgG-binding epitopes recognized by immunoglobulin G were not disclosed [15,16]. In this work, IgG-binding results are presented derived from a proprietary laser-printed peptide microchip containing overlapping peptides from immunologically important EBV proteins to illustrate the potential of this new technology.…”
Section: Discussionmentioning
confidence: 94%
“…Presently, the standard of diagnosis for many autoimmune diseases is based on ANA (anti-nuclear antibody) assays in which immunoglobulin binding is characterized against the cell cytoplasm and nucleus and related IgG binding assays. While ANA and immunoassay technology can in principle be automated, a more recent approach is the use of specific antigenic host and viral proteins David H. Dreyfus printed in a microarray with sensitivity similar or great than that of the ANA [15,16]. Using proteomic technology, hundreds or even thousands of epitopes can be analyzed simultaneously with a single serum sample.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The test is validated as a clinical test to exclude a diagnosis of SLE if no compelling clinical evidence exists or to support a low likelihood of SLE. 37 …”
Section: Systemic Lupus Erythematosus (Sle)mentioning
confidence: 99%
“…We pursued one such application of protein profiling in SLE with the use of iCHIP microarray technology for the development, verification, and validation of a definitive serologic rule-out diagnostic test: the SLE-Key rule-out test [88]. …”
Section: Novel Sle Testingmentioning
confidence: 99%